POLITICS OF BIOPIRACY: AN ADVENTURE INTO HOODIA/XHOBA PATENTING IN SOUTHERN AFRICA - Amusan, Lere (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Africa is being described as the wretched of the earth, despite this, the continent is endowed with naturalresources, dynamic ecosystem, and different species of plants and animals, and species derivatives. This paper area ofdeparture is to focus on Hoodia, a plant that is being a source of food, medicine and water for the San and Khoeindigenous peoples before the advent of Europeans into southern Africa. South African Council for Scientific andIndustrial Research (CSIR) dubiously patented Hoodia without observing the basic indices of geographical indications(GIs), indigenous knowledge (IK), novelty, access sharing benefit (ASB), prior informed consent (PIC) and sustainabilityof ecosystem before the rights was sold to Phytopharm pharmaceutical company.Materials and methods: This article adopts neoliberal thesis with emphasis on complex interdependence theory oforganic linkages between developing and developed countries. Secondary sources of information taken into account ofqualitative and critical discuss content analyses dominate this paper.Result: The paper recommends a linkage between developed and developing states based on endowment theory andcomparative advantage with the notion of adhering to the Convention on Biological Diversity (CBD) which has threeobjectives: the conservation of biodiversity; the sustainable utilisation of indigenous biological resources (IBR); and fairand equitable benefit sharing.Conclusion: The paper recommends that there is a need to follow CBD and other relevant international regimes thatpromote equal exchange in exploitation of Africa resources as against the present skewed arrangement that is in favour ofmultinational corporations (MNCs).